(untitled) (Научни трудове на УНСС, 2019)
The article deals with the topic and topos of the 24/7 city. Notwithstanding, a tendency for extended times the rather inconclusive evidence of a leveling of day time and night time activity incessance or 24/7 is a highly selective urban phenomenon – functionally, spatially, socially and temporally. The selectivity of 24/7 leads also to a e selectivity and concentration of conflicts during the night. Night governance has to provide two public conflicting public goods: the access to the night (the night as a timespace of possibilities, of extended options) the protection of the night (the night as a timespace or rest, repair, calmness and darkness). The provision of these public goods has to take the three classic sustainability dimensions into account. This requires an integrative and transversal governance of the urban night.